2004
DOI: 10.4049/jimmunol.172.8.4821
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation of CD8 T Cell Responses by OX40

Abstract: The persistence of functional CD8 T cell responses is dependent on checkpoints established during priming. Although naive CD8 cells can proliferate with a short period of stimulation, CD4 help, inflammation, and/or high peptide affinity are necessary for the survival of CTL and for effective priming. Using OX40-deficient CD8 cells specific for a defined Ag, and agonist and antagonist OX40 reagents, we show that OX40/OX40 ligand interactions can determine the extent of expansion of CD8 T cells during responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
149
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(165 citation statements)
references
References 36 publications
13
149
2
Order By: Relevance
“…In our studies we demonstrate that OX40L contributes to the enhancement of antigen-dependent IFN-c production by CpG-stimulated PDC both in NKT cells and CD8 T cells. Our data extend earlier studies in the literature in which OX40-mediated costimulation was found to regulate the accumulation of antigen-stimulated CD8 cells [61]. Of note, in our studies the Th1 cytokine IFN-a was required (but not sufficient) for the PDC-mediated enhanced IFNc production in NKT cells.…”
Section: Discussionsupporting
confidence: 90%
“…In our studies we demonstrate that OX40L contributes to the enhancement of antigen-dependent IFN-c production by CpG-stimulated PDC both in NKT cells and CD8 T cells. Our data extend earlier studies in the literature in which OX40-mediated costimulation was found to regulate the accumulation of antigen-stimulated CD8 cells [61]. Of note, in our studies the Th1 cytokine IFN-a was required (but not sufficient) for the PDC-mediated enhanced IFNc production in NKT cells.…”
Section: Discussionsupporting
confidence: 90%
“…The function of this co-stimulatory receptor has mostly been studied in CD4 T cells, but has also been shown to enhance CD8 T cell responses [43,44]. As OX40 ligand is expressed by B cells, the CXCR5 + CD8 T cells could be positively regulated by B cells in the follicle via this receptor pair [45].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both receptors are expressed on CD8 1 T cells following TCR signalling and appear to have similar roles in activation [31] with agonistic mAb directly enhancing CD8 1 T-cell responses, largely through improved survival of antigen-activated T cells [30,41]. Both 4-1BB and OX40 interact with common TRAF proteins, activate NFkB pathways and induce expression of anti-apoptotic Bcl-2 family molecules [42][43][44].…”
Section: Discussionmentioning
confidence: 99%